New occurrence of Mitracarpus frigidus (Willd. ex Roem. and Schult.) K.Schum. (Rubiaceae, Spermacoceae) in the State of Ceará, Brazil - Rodrigues, Leonardo de Sousa; de Sousa, Izaias Carvalho [UNESP]; Santos, Francisco Diego Sousa (FapUNIFESP (SciELO), 2023)
(New occurrence of Mitracarpus frigidus (Willd. ex Roem. and Schult.) K.Schum. (Rubiaceae, Spermacoceae) in the State of Ceará, Brazil). We report a new occurrence of Micracarpus frigidus (Willd. ex Roem. and Schult. K.Schum. in the Brazilian State of Ceará, collected at the Serra das Matas residual massif. We present data on its morphological relationship to a similar species, ecological preferences, photographs, illustration, map and updated information on its distribution. This finding increases our knowledge on the distribution of this species and about the flora of Ceará State, as well as aiding in future biogeographic research.
Nova ocorrência de Mitracarpus frigidus (Willd. ex Roem. & Schult.) K.Schum. (Rubiaceae, Spermacoceae) no Estado do Ceará, Brasil
Keywords: new records; residual massif; rocky outcrop; serra das matas